2020
DOI: 10.3390/life10090200
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preconditioning Attenuates the Response to Experimental Colitis and Modifies Composition of Gut Microbiota in Wild-Type Mice

Abstract: This study investigated the suppressive effect of exercise preconditioning against colitis induced by high-fat diet (HF) plus dextran sulfate sodium (DSS) in wild-type mice. Male mice (C57BL/6) aged 6 weeks were assigned to standard chow (SC, n = 10) or HF (n = 10) or HF followed by DSS (HF+DSS, n = 10) or exercise preconditioning (EX) followed by HF+DSS (EX+HF+DSS, n = 10) for a total of 15 weeks. After 12 weeks of dietary treatments and/or exercise preconditioning, mice in the DSS groups were subjected to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…A prebiotics study in overweight and obese children found B. vulgatus was significantly correlated with fat and found to be depleted following the intervention (Nicolucci et al, 2017). Exercise also decreased B. vulgatus in a mouse model of colitis (Cho et al, 2020). This suggests that B. vulgatus is associated with obesity and that a decrease in its prevalence via exercise signifies an improvement in host health, as seems to have also been the case in our study.…”
Section: Discussionsupporting
confidence: 84%
“…A prebiotics study in overweight and obese children found B. vulgatus was significantly correlated with fat and found to be depleted following the intervention (Nicolucci et al, 2017). Exercise also decreased B. vulgatus in a mouse model of colitis (Cho et al, 2020). This suggests that B. vulgatus is associated with obesity and that a decrease in its prevalence via exercise signifies an improvement in host health, as seems to have also been the case in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, enlarged spleen and increased splenic myeloid and Th17 cells were observed in HFHS-fed mice, whereas they were decreased in MLNs, suggesting that immune cells may be mobilized on the inflammation site, i.e., the colon, similar to what has been observed with HF-induced colonic dysbiosis ( 38 ). It would have been necessary to explore this hypothesis by performing IHC stainings of flow cytometry on colons samples, it is one of the limitations of our study.…”
Section: Discussionsupporting
confidence: 51%
“…The increased levels of Bacteroides vulgatus, which were observed during COVID-19 infection compared to samples collected three weeks following a negative PCR test, could suggest that the infection could result in subsequent infiltration of acute inflammatory cells through the gut barrier and result in the development of colitis symptoms [49].…”
Section: Discussionmentioning
confidence: 99%